Effect of rotation on wave propagation in fibre-reinforced viscothermoelastic media of higher order - Zahra S. Hafed; S.M. Abo-Dahab; A.M. Abd-Alla; Sameh E. Ahmed; Adnan Jahangir; Mohamed A. Aiyashi (Alexandria Engineering Journal, 2023)
The purpose of the current study is to establish a novel mathematical model in the wave propagation in fibre-reinforced viscothermoelastic media of higher order. The governing equations of a fibre-reinforced viscothermoelastic media of higher order are solved analytically to determine mechanical displacement and stresses. Dispersion relation for Rayleigh-type, Love-type, and Stoneley-type wave has been derived using suitable boundary conditions, which is found to be complex in nature. The analysis included Rayleigh-type, Love-type, and Stoneley-type waves while the findings revealed a broader scope compared to previous research, which is encompassed by our results as special cases. Findings are compared with and without rotational effect, along with assessing the parameters for fiber-reinforced materials in the medium, it was observed that surface waves could not propagate in a fast rotating medium. These results are computed numerically and depicted graphically to highlight the effects of fiber reinforcement and rotation parameter on the surface wave speed. Certain particular cases of interest have been deduced from the current investigation. Numerical results and graphical analyses of surface waves were performed using MATLAB software.